Effects of mixed fermentation of non-Saccharomyces and Saccharomyces cerevisiae on color and flavor of coix seed wine mash - XIAO Fucai, LI Yingkui, LIU Kai, GU Junhua, WANG Jing (Zhongguo niangzao)
The effects of single fermentation of commercial Saccharomyces cerevisiae (SC), and mixed fermentation of commercial S. cerevisiae (SC) with non-Saccharomyces Torulaspora delbrueckii (TD), Issatchenkia orientalis (IO) and Schizosaccharomyces pombe (SP) on the basic physicochemical properties, color and volatile flavor substances of coix seed wine mash were investigated. The results showed that compared with the SC group, mixed fermentation could reduce the alcohol content, pH and reducing sugar content of coix seed wine mash, and increase the brightness of the wine mash. The types of volatile flavor substances were significantly increased by mixed fermentation, especially esters (P<0.05). 43, 49, 48 and 48 volatile flavor substances were detected in the SC group, the TD+SC group, the IO+SC group and the SP+SC group, respectively. Among them, the contents of phenylacetaldehyde, nonanal and 3-hydroxy-2-butanone were significantly increased in the SP+SC group (P<0.05). The biomark compounds were 1-pentanol, 2,3-butanediol, phenethyl alcohol, etc in SC group, n-decanol, 2-methyl butanol, diethyl succinate, etc in the TD+SC group, isovaleric acid, ethyl benzoate, ethyl phenylacetate, etc in the IO+SC group, and acetic acid isobutyl ester, ethyl butyrate, phenylacetaldehyde, etc in the SP+SC group. In conclusion, the mixed fermentation of non-Saccharomyces and commercial S. cerevisiae was helpful to improve the color and flavor quality of coix seed wine mash.